Alcohol use among older adults: SABE cohort study, São Paulo, Brazil. - Gabriela Arantes Wagner; Maria Lucia Lebrão; Yeda Aparecida de Oliveira Duarte; Dirce Maria Trevisan Zanetta (PLoS ONE)
In recent years, Brazil has demonstrated a new demographic pattern characterized by a reduction in both birth and mortality rates and a significant increase in the number of older adults. The purpose of the present study was to describe the frequency of alcohol intake in a representative sample community of older adults in the city of São Paulo, Brazil, followed over a six-year period. A prospective Saúde, Bem-Estar e Envelhecimento (SABE [Health, Wellbeing and Aging]) cohort study conducted in 2000 and 2006 in City of São Paulo, Brazil. 2,143 individuals aged 60 years or older selected through multi-stage sampling in the year 2000 (41.4% male and 58.6% women) and 1,115 individuals belonging to the follow-up cohort evaluated in 2006. The frequency of alcohol intake in the previous three months was obtained through self-reports of interviewees. The results demonstrate that in 2000, alcohol consumption was less than one day a week among 79.7% of the sample, one to three days a week among 13.0% and four or more days a week among 7.3%. In agreement with findings on other populations, consumption four or more days a week was more frequent among the male gender as well as those with greater schooling and income and good self-rated health (p<0.05). The longitudinal analysis demonstrated an increase in the frequency of alcohol consumption one to three times a week among the individuals in the 2006 follow-up study. In the present population-based sample, alcohol intake was low and the frequency of moderate alcohol consumption increased over the years. The present study can assist understanding the changes in alcohol intake among older adults throughout time and the ageing process.